The effect of Temperature Drying of Seaweed, Addition of Calcium Hypochlorite, and Potassium Hydroxide on the Quality of Semi-Refined Carrageenan Products - Heriyanto, Heri; Astria, Windi; Fattah, Hanif Al; Suhendi, Endang (World Chemical Engineering Journal, 2023)
Indonesia is a major producer of Eucheuma cottonii seaweed, yet its utilization remains suboptimal. Approximately 80% of seaweed exports consist of raw materials with low market value. The research aims to enhance the quality and market value of seaweed by transforming it into semi-refined carrageenan products. The method used for carrageenan production involves extraction using a KOH solution with different concentration levels using 5%, 7.5%, and 10% (w/v), along with drying temperatures ranging from 80°C to 90°C. Additionally, bleaching treatment is applied using calcium hypochlorite with concentration level using 1.5% and 2.5% (w/v). The analyses conducted include water content, ash content, yield, viscosity, gel strength, and degree of whiteness. The optimal results for semi-refined carrageenan, based on yield analysis, water and ash content, gel strength, viscosity, and degree of whiteness, were obtained from samples with a KOH concentration of 10%, calcium hypochlorite concentration of 1.5%, and drying temperature of 80°C.